Activación de dos herbicidas y su incidencia en el control de caminadora (Rottboellia exaltata (L)) en un cultivo de sorgo (Sorghum bicolor (L) Moench) ubicado en un suelo de vega (1991)
An axperiment with growing chicks was conducted at ICA 's experiment station, Tibaitata, in the [Jo gota ploteau, to study the effect af adding cy~ nide (363 mg KCN/kg) and tann;ns ( 10 g/kg) to sorghum and corn basedrations, and the oction of thiosulfate and choline in preventing the toxic - effects of cyanide and tonnias respectively.